2018
DOI: 10.1016/j.bjm.2017.06.009
|View full text |Cite
|
Sign up to set email alerts
|

A new coumarin derivative, 4-acetatecoumarin, with antifungal activity and association study against Aspergillus spp.

Abstract: Fungal infections have become a concern for health professionals, and the emergence of resistant strains has been reported for all known classes of antifungal drugs. Among the fungi causing disease, we highlight those that belong to the genus Aspergillus. For these reasons, the search for new antifungals is important. This study examines the effects of a coumarin derivative, 4-acetatecoumarin (Cou-UMB16) both alone and together with antifungal drugs, and its mode of action against Aspergillus spp. Cou-UMB16 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The mode of action of furanocoumarins has not been studied despite increased interest in this type of compound. However, there has been research into the mode of action research of their antifungal activity …”
Section: Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…The mode of action of furanocoumarins has not been studied despite increased interest in this type of compound. However, there has been research into the mode of action research of their antifungal activity …”
Section: Chemistrymentioning
confidence: 99%
“…However, there has been research into the mode of action research of their antifungal activity. 44,45 New structure-activity relationship (SAR) studies on coumarins allowed their antifungal activity to be attributed to two factors: O-substitution, which is essential; and a short aliphatic chain and electron-withdrawing groups, which improve activity. 46 that alters respiratory functions.…”
Section: Flavonoidsmentioning
confidence: 99%
“…[100,101] Felipe Q.S. Guerra et al (2018) investigate the beneficial effects of A47 against Aspergillus spp., either alone or in combination with some other antifungal medications. The effects of A47 on the growth of mycelia and the germination of fungal conidia from Aspergillus spp.…”
Section: Antifungal Capacity Of Pdcsmentioning
confidence: 99%
“…Although propolis possesses efficient biological properties such as antibacterial, antioxidation, anti-inflammatory, antitumor, etc., the applications were still limited due to its hydrophobicity. Sharaf encapsulated HBP in the cavity of β-CD, mixed it with κ-CAR, and then used glyoxal as a cross-linked agent to generate a hydrogel with high water retention, high swelling rate, antibacterial properties, controllable and continuous release of HBP, which had great potential in promoting tissue repair and regeneration . COU is a bioactive compound found in soybean, alfalfa, and other leguminous species with a variety of pharmacological activities including antifungal, , antiherpes, , anti-inflammatory, etc. Bianchi et al evaluated the effects of hydroxypropyl methylcellulose hydrogel loaded with the COU/β-CD inclusion complex on wound healing, the in vitro cell scratching experiments, and the in vivo contraction of the skin wound area of Wistar rats have demonstrated that the prepared hydrogel could promote rapid tissue repair and regeneration .…”
Section: Cd-based Drug Delivery Hydrogelsmentioning
confidence: 99%